Young children spontaneously invent three different types of associative tool use behaviour. (7th February 2022) - Reindl, E.; Tennie, C.; Apperly, I. A.; Lugosi, Z.; Beck, S. R.
Abstract: Abstract: Associative Tool Use (ATU) describes the use of two or more tools in combination, with the literature further differentiating between Tool set use, Tool composite use, Sequential tool use and Secondary tool use. Research investigating the cognitive processes underlying ATU has shown that some primate and bird species spontaneously invent Tool set and Sequential tool use. Yet studies with humans are sparse. Whether children are also able to spontaneously invent ATU behaviours and at what age this ability emerges is poorly understood. We addressed this gap in the literature with two experiments involving preschoolers (E1, N = 66, 3 years 6 months to 4 years 9 months; E2, N = 119, 3 years 0 months to 6 years 10 months) who were administered novel tasks measuring Tool set, Metatool and Sequential tool use. Participants needed to solve the tasks individually, without the opportunity for social learning (except for enhancement effects). Children from 3 years of age spontaneously invented all of the types of investigated ATU behaviours. Success rates were low, suggesting that individual invention of ATU in novel tasks is still challenging for preschoolers. We discuss how future studies can use and expand our tasks to deepen our understanding of tool use and problem-solving in humans and non-human animals.